1996
DOI: 10.1038/bjc.1996.336
|View full text |Cite
|
Sign up to set email alerts
|

Daunorubicin and doxorubicin but not BCNU have deleterious effects on organotypic multicellular spheroids of gliomas

Abstract: Summary In the present study organotypic multicellular spheroids (OMS) were used to study the effects of chemotherapeutic agents on malignant gliomas. Compared with the frequently used cell line models, OMS have several advantages with respect to the preservation of the cellular heterogeneity and the structure of the original tumour. OMS prepared from seven glioma specimens were treated with 1,3-bis(2-chloroethyl)-1-nitrosourea (BCNU), daunorubicin or doxorubicin. After exposure to these drugs, the histology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Moreover, the cytotoxicity of doxorubicin in organotypic multicellular spheroids of human gliomas appeared to be higher than that of BCNU (carmustin). 56 We have recently demonstrated that the toxicity of doxorubicin bound to nanoparticles was rather lower than that of a solution of doxorubicin in saline. 35 In the present study, we found only limited systemic toxicity that was dose-dependent and obviously not enhanced but rather alleviated by polysorbate coating of nanoparticles.…”
Section: No Indication Of Drug-related Neurotoxicitymentioning
confidence: 99%
“…Moreover, the cytotoxicity of doxorubicin in organotypic multicellular spheroids of human gliomas appeared to be higher than that of BCNU (carmustin). 56 We have recently demonstrated that the toxicity of doxorubicin bound to nanoparticles was rather lower than that of a solution of doxorubicin in saline. 35 In the present study, we found only limited systemic toxicity that was dose-dependent and obviously not enhanced but rather alleviated by polysorbate coating of nanoparticles.…”
Section: No Indication Of Drug-related Neurotoxicitymentioning
confidence: 99%
“…In several studies, tumor fragment spheroids were shown to maintain tumor markers and viability better than either monolayers or multicellular spheroids (12)(13)(14)17). In a few cases, the effect of different treatments has been studied-for example, on the proliferation or histology of the tumor (13,(18)(19)(20). We are not aware of any study in which tumor fragment spheroids were specifically examined for apoptosis, although this in vitro model has much promise for such studies.…”
mentioning
confidence: 99%
“…More recently, the therapeutic effect and diffusion of various selectively replicative (Bauerschmitz et al, 2002;Grill et al, 2002) and nonreplicative (Enger et al, 2002;van Beusechem et al, 2002) viral gene therapy vectors have been studied. Even though systematic studies of the binding, distribution, and chemotherapeutic effect of 23 Engineering Lipid Vesicles of Enhanced Intratumoral Transport Capabilities doxorubicin and daunorubicin (Kaaijk et al, 1996;Wartenberg et al, 1998), two therapeutic molecules clinically used in their liposome-encapsulated form for treatment of Kaposi sarcomas and being developed also for other cancer types (Tejada-Berges et al, 2002), have been published, no systematic study has described the interaction of tumor spheroids with delivery systems or liposomes in particular.…”
Section: Discussionmentioning
confidence: 99%